AI DAN IA: AKANKAH PERAN INTERNAL AUDITOR TERGANTIKAN OLEH ARTIFICIAL INTELLIGENCE? - Anggraeni, Rima Melati (STIE Perbankan Indonesia, 2024)
In the era of digital transformation, the rapid development of artificial intelligence (AI) technology has had an impact on all fields, including the field of internal audit. AI offers new opportunities for internal auditors in analyzing large amounts of data, identifying risks, and increasing accuracy and efficiency in carrying out audit tasks. However, behind all these benefits, there is the question of whether the role of internal auditors will gradually be replaced by AI. This research will explore the opportunities and challenges that arise with the integration of AI in the internal audit process. By using a literature review method, this research aims to analyze the extent to which the role of AI influences the efficiency and accuracy of internal audits. The research results show that there is a paradigm shift in the use of AI by auditors. This research provides valuable insight into the ongoing discussion about the transformative effects of AI in internal auditing. Keywords: Artificial Intelligence, Internal Audit, Efficiency, Digital Transformation